Range of motion in the cervical spine after odontoid fracture treated with anterior screw fixation - Andżelina Wolan-Nieroda; Andrzej Maciejczak; Agnieszka Guzik; Grzegorz Przysada; Ewa Szeliga; Mariusz Drużbicki (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background It is believed that direct odontoid screw fixation preserves the physiological cervical range of motion following surgery. However, there are no clinical studies confirming the motion sparing value of this technique. This study aims to (1) to assess active cervical range of motion following types II and III odontoid fracture, successfully treated with anterior odontoid screw fixation, and (2) to examine the relationship between the range of motion of the head and duration of collar usage, neck pain, quality of life, and patients’ age. Methods The study involved 41 patients subjected to a procedure of direct osteosynthesis of the dens with lag screw. Following the operation all the patients had to wear a cervical collar to protect the osteosynthesis. The control group consisted of 41 individuals with no clinical diagnosis of any cervical spine disorders. The spinal motion was assessed using multi-cervical unit, taking into account bending/extension, left and right lateral flexion, and left and right axial rotation. Results In the study group, spine mobility correlated with the duration of hard collar usage following the operation, with a longer duration corresponding to poorer spine mobility at the end of the treatment. Statistically significant correlation was observed in the case of extension (p < 0.021) and axial rotation (p < 0.007). In the study group, there was a negative correlation between the range of motion and the patients’ age, i.e., the older the patient the poorer his/her spinal mobility (p < 0.001). Conclusions Active cervical range of motion in patients following direct osteosynthesis of the dens, augmented with a hard collar, was significantly lower than in the control population, and it correlated negatively with the duration of collar usage, the patients’ age, and intensity of spinal pain.